2008 IEEE Power and Energy Society General Meeting - Conversion and Delivery of Electrical Energy in the 21st Century 2008
DOI: 10.1109/pes.2008.4596124
|View full text |Cite
|
Sign up to set email alerts
|

Selected studies on offshore wind farm cable connections - challenges and experience of the Danish TSO

Abstract: The Danish power system is characterised by a high share of wind power production. Most of the wind power has so far been distributed onshore and connected to the lower voltage levels. The recent tendency is to group it in large offshore wind farms. The wind farms are often connected directly to the high voltage network via long AC cable lines compensated by shunt reactors. These cable connections impose some additional challenges that should be considered in the planning stage. This paper presents the recent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 3 publications
0
26
0
Order By: Relevance
“…the Smart Wind consortium which is developing the Hornsea zone in the North Sea has indicated that it is under consideration and the Crown Estate has suggested that it can be competitive [17] [18]. The Horns Rev B wind farm in Denmark has also set a precedent for such an arrangement by employing a 100km AC cable connection with a compensating reactor near the cable mid-point [11] although the cable connection in this case consists of 42km of subsea cable and 58km of onshore cable and the mid-point compensating reactor is located onshore. The addition of reactive compensation at SSB2, in equal quantity to that at the wind farm end of the cable, divides the cable reactive power production in three.…”
Section: B Location Of Reactive Compensationmentioning
confidence: 99%
See 1 more Smart Citation
“…the Smart Wind consortium which is developing the Hornsea zone in the North Sea has indicated that it is under consideration and the Crown Estate has suggested that it can be competitive [17] [18]. The Horns Rev B wind farm in Denmark has also set a precedent for such an arrangement by employing a 100km AC cable connection with a compensating reactor near the cable mid-point [11] although the cable connection in this case consists of 42km of subsea cable and 58km of onshore cable and the mid-point compensating reactor is located onshore. The addition of reactive compensation at SSB2, in equal quantity to that at the wind farm end of the cable, divides the cable reactive power production in three.…”
Section: B Location Of Reactive Compensationmentioning
confidence: 99%
“…These include three-phase AC cables at line voltages of 145kV and up to 162 km in length. Moreover, consideration is being given to ways in which the problems associated with long AC cables might be overcome, including use of mid-point compensation to reduce voltages and losses [11]. Meanwhile, one of the first planned HVDC connections of an offshore wind farm, BorWin1, was originally expected to be operational in 2009 but is, as of November 2014, reported by ABB to be planned for commissioning in 2015 [6] with a number of problems having been reported including overcurrent in a filter, a fire and "'dirty electricity' affecting the substation" [12].…”
Section: Introductionmentioning
confidence: 99%
“…Operation of a lossless CL with different terminal voltages implies an asymmetrical reactive power profile, with more reactive power flowing towards the terminal at lower voltage: due to the uneven loading of the CL, maximum active power transmission decreases with respect to the value given by (3). For a given couple of terminal voltages (U S , U R ), steady state operating limits in terms of active power transmission are given by:…”
Section: Lossless Analysismentioning
confidence: 99%
“…Fig. 6b shows (U R , P) curves for the 100 km long CL, with sending end voltage U S = 400 kV; the left and right curves refer to the current limit being reached at the sending end and at the receiving end respectively, and in the lossless case meet for U R = U S at the maximum value given by (3). The portion of the (U, P) plane enclosed by the curves defines the steady state safe operating area of the CL (for U S = 400 kV); circle diagrams in the (P, Q) plane [12,13] can also be used to the same purpose.…”
Section: Lossless Analysismentioning
confidence: 99%
See 1 more Smart Citation